The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1975
DOI: 10.1111/j.1550-7408.1975.tb05225.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Pirhemocyton Chatton & Blanc and other, Possibly Related, Infections of Poikilotherms

Abstract: SYNOPSIS. Data for host and geographic distribution are listed for Pirhemocyton and for apparently similar infections of poikilothermic vertebrates. The list was compiled from published accounts of Pirhemocyton, Toddia, Cytamoeba, Bertarellia, Piscine erythrocytic necrosis, Immanoplasma, Haematractidium, Sauroplasma, Sauromella, Serpentoplasma, Tunetella, Haemohormidium and unnamed infections. New records are included for Pirhemocyton and Haematractidium. The probability that some may be viruses and not protoz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
29
1
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 37 publications
5
29
1
1
Order By: Relevance
“…Since the parasite found in the current study comes from a flatfish, it has a loop-like structure between some nuclei as in So's (1972) illustrations, and it resembles Siddall et al 's (1994) light micrographs of H. terraenovae, it is logical to identify it provisionally as this organism. Its likeness to Haematractidium scombri Henry, 1910 is also noted (see Henry 1910, 1913c, Johnston 1975, MacLean 1980, Davies 1995. However, extracellular forms, like those seen in our material, were not recorded by any authors who previously reported H. terraenovae.…”
mentioning
confidence: 40%
See 1 more Smart Citation
“…Since the parasite found in the current study comes from a flatfish, it has a loop-like structure between some nuclei as in So's (1972) illustrations, and it resembles Siddall et al 's (1994) light micrographs of H. terraenovae, it is logical to identify it provisionally as this organism. Its likeness to Haematractidium scombri Henry, 1910 is also noted (see Henry 1910, 1913c, Johnston 1975, MacLean 1980, Davies 1995. However, extracellular forms, like those seen in our material, were not recorded by any authors who previously reported H. terraenovae.…”
mentioning
confidence: 40%
“…They are often irregularly round in shape, exhibit peripheral staining with Romanowsky dyes, and show evidence of intraerythrocytic division (Henry 1913b, Laird and Bullock 1969, So 1972, Davies 1980, Barta 1991. Khan (1980Khan ( , 1984 demonstrated transmission of Haemohormidium beckeri So, 1972 and similar infections between fishes by haematophagous leeches, believing the blood parasites to be piroplasms, but controversy has remained surrounding the taxonomy of the genus Haemohormidium and the equally enigmatic genus Haematractidium Henry, 1910(see Henry 1910, 1913c, Johnston 1975, MacLean 1980, Bodammer and MacLean, 1985, Davies 1995. This uncertainty was summarised by Siddall et al (1994) who concluded that Haemohormidium and Haematractidium are synonymous genera, with the former taking priority; moreover, the identity of these parasites was not established, but they were not considered apicomplexan.…”
mentioning
confidence: 99%
“…27 Reptile EIVs have been reported in diverse squamate species. 18,36,37 Similarly in amphibians, Frog erythrocytic virus, which causes intraerythrocytic intracytoplasmic inclusions, is an iridovirus that does not belong to the genus Ranavirus. 5,10,32 Frog erythrocytic virus has been shown to measure 293-312 nm 32 ; this is larger than PvEIV, which measures 141-193 nm.…”
Section: Discussionmentioning
confidence: 99%
“…37 Within the family Agamidae, EIVs have been found in the Bibron's agama (Agama impalearis) 2 and the common agama (A. agama). 18,26 In some cases, erythrocytic inclusions have been associated with marked anemia, 17,26 but experimental infection has failed to reproduce anemia unless the lizards were maintained in a cold environment. 3 Many viral diseases of poikilothermic vertebrates are highly temperature dependent, including iridoviruses, and the current data does not differentiate among the relative roles of host and virus on temperature-dependence of disease.…”
Section: Introductionmentioning
confidence: 99%
“…Although descriptions are not well documented and host records confused, small intracytoplasmic inclusions, attributed to viral erythrocytic necrosis (VEN), have been reported in stained blood smears of erythrocytes from the small-spotted catshark Scyliorhinus canicula (Johnston 1975) and the little skate Raja erinacea (Khan & Newman 1982). McAllister & Stoskopf (1993) describe sharks with low hematocrits, pale gills and organs, and hyperplastic hematopoietic tissues.…”
Section: Introductionmentioning
confidence: 99%